1951
DOI: 10.1152/ajplegacy.1951.168.1.131
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Anuria Occurring During Apnea Under Diffusion Respiration

Abstract: The APS Journal Legacy Content is the corpus of 100 years of historical scientific research from the American Physiological Society research journals. This package goes back to the first issue of each of the APS journals including the American Journal of Physiology, first published in 1898. The full text scanned images of the printed pages are easily searchable. Downloads quickly in PDF format.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1955
1955
1976
1976

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The role of the renal mechanism in combating the disturbances in acid-base equilibrium must be negligible since we found that urine production practically ceased during diffusion respiration. Whitehead et al (1948) and Kopecky, Rayburn, Whitehead & Draper (1952) have also reported that anuria developed during diffusion respiration. It is unlikely that anoxia was responsible for this anuria as the anuria was always complete within 10 min of the beginning of diffusion respiration, at a time when the arterial 02 saturation was normal.…”
Section: Effect Of Breathing High C02 Mixtures On the Logarithmic C02mentioning
confidence: 95%
“…The role of the renal mechanism in combating the disturbances in acid-base equilibrium must be negligible since we found that urine production practically ceased during diffusion respiration. Whitehead et al (1948) and Kopecky, Rayburn, Whitehead & Draper (1952) have also reported that anuria developed during diffusion respiration. It is unlikely that anoxia was responsible for this anuria as the anuria was always complete within 10 min of the beginning of diffusion respiration, at a time when the arterial 02 saturation was normal.…”
Section: Effect Of Breathing High C02 Mixtures On the Logarithmic C02mentioning
confidence: 95%